Losses and gains to developing countries from the migration of educated workers: An overview of recent research, and new reflections - Oded Stark; C. Simon Fan (University of Warsaw, Centre of Migration Research (CMR), 2007)
This paper synthesizes and extends recent research on 'The New Economics of the Brain Drain.' In a unified framework, the paper shows that while recently identified adverse repercussions of the brain drain exacerbate the long-recognized negative impact of the brain drain, longer-term consequences turn the brain drain into the harbinger of powerful gains. These gains have been studied already in recent research, or merit attention in future research.
Keywords: F22; I30; J24; J61; J64; O15; 330; International migration; Human capital formation; Overeducation; 'Educated unemployment'; Beneficial brain drain; Social welfare; Brain Drain; Hochqualifizierte Arbeitskräfte; Entwicklungsländer